Engineering a promiscuous prenyltransferase for selective biosynthesis of an undescribed bioactive cannabinoid analog - Qin Yan; Yue-Gui Chen; Xiao-Wen Yang; An Wang; Xiao-Ping He; Xue Tang; Hong Hu; Kai Guo; Zong-Hua Xiao; Yan Liu; Sheng-Hong Li (Communications Biology)
Abstract Cannabinoids are unique meroterpenoids, with cannabigerolic acid (CBGA) serving as a dedicated precursor. This study introduces a fungal aromatic prenyltransferase AscC into the engineered Escherichia coli to catalyze the transfer of C5-C15 terpenoid linear precursors to olivetolic acid. Four CBGA derivatives (compounds 1–4) with diverse C5, C10, or C15 prenyl chains are isolated and identified, with compound 4 being an undescribed product featuring a C15 prenyl chain at the C-5 position. Compound 4 demonstrates the highest anti-neuroinflammatory and antibacterial activities, with IC50 values of 3.06 µM for TNF-α and 4.31 µM for IL-6, alongside EC50 values ranging from 0.87 to 3.16 µM against three Gram-positive bacteria. An efficient construct is established by incorporating an additional copy of AscC, resulting in a yield of 14.85 ± 0.91 mg/L of compound 4. Two mutants, L180Y and L180F, are engineered to selectively produce compound 4. These findings provide a foundation for enriching the chemical diversity of bioactive cannabinoid analogs with various prenyl moieties through combinatorial biosynthesis.